2021
DOI: 10.1021/acsaem.0c03190
|View full text |Cite
|
Sign up to set email alerts
|

CuS Nanosheet Arrays for Electrochemical CO2 Reduction with Surface Reconstruction and the Effect on Selective Formation of Formate

Abstract: Copper-based catalysts have shown excellent performance in electrochemical CO 2 reduction, but there has not been much study on copper sulfides. In our work, a simple and low-temperature chemical bath deposition method was used to fabricate CuS nanosheet arrays on brass, on which a Faradaic efficiency over 70% and a production rate over 50 mA•cm −2 for formate were obtained at a low potential of −0.7 V vs RHE when used as a catalytic electrode for CO 2 reduction. During the CO 2 reduction process, CuS nanoshee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 48 publications
(67 reference statements)
0
27
0
Order By: Relevance
“…To calculate the energy conversion efficiency for CO 2 electroreduction, we examined the literature using the CAS SciFinder software and calculated the efficiencies in 107 typical aqueous and semi-aqueous systems. 13–73 We selected the literature reports with a relatively high frequency of citations over the last 30 years. The pH of each CO 2 -saturated solution required for the calculation in this work was measured using an F-53 pH meter (HORIBA, Ltd).…”
Section: Theoretical and Experimentalmentioning
confidence: 99%
See 1 more Smart Citation
“…To calculate the energy conversion efficiency for CO 2 electroreduction, we examined the literature using the CAS SciFinder software and calculated the efficiencies in 107 typical aqueous and semi-aqueous systems. 13–73 We selected the literature reports with a relatively high frequency of citations over the last 30 years. The pH of each CO 2 -saturated solution required for the calculation in this work was measured using an F-53 pH meter (HORIBA, Ltd).…”
Section: Theoretical and Experimentalmentioning
confidence: 99%
“…3282 | Anal. Methods, 2022,14,[3280][3281][3282][3283][3284][3285][3286][3287][3288] This journal is © The Royal Society of Chemistry 2022 over the last 30 years were considered in this calculation. The pH of Naon was obtained from the literature 74.…”
mentioning
confidence: 99%
“…In 2021, Dou and his group bath-deposited CuS nanosheets on brass mesh, which on electrocatalysis was rapidly reconstructed to a nanowire network. 192 A DFT study suggested that the Cu(111) plane and residual sulfur (Raman data conrmed the presence of S residue) weakened the adsorption of HCOO* and *COOH intermediates; therefore, formate was formed without further reaction proceeding to CO. The electrocatalyst could provide a commendable high current density of 75 mA cm −2 at −0.7 V RHE with 67.8 AE 1% FE towards formate, while CO and CH 4 FE were less than 1%.…”
Section: Electrocatalytic (Ec) Systemsmentioning
confidence: 99%
“…26 There are many recent works on Cu x S y applications in the newly emerging research fields created by the current economic and environmental issues, such as solar cells, photovoltaics, photocatalysts, photothermal agents, and electrocatalysts for the HER and CO 2 reduction reactions. [30][31][32][33][34][35][36][37][38] A few studies were performed to explore the applicability of Cu x S y for the HER and CO 2 reduction, which revealed that Cu-based materials could be used in energy storage devices and major CO 2 converters. 30,[39][40][41] In most previous works, Cu x S y was prepared by a conventional hydrothermal method, chemical bath deposition, and wet-chemical route.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Cu 2 S does not exhibit any localized surface plasmon resonance (LSPR) 26 . There are many recent works on Cu x S y applications in the newly emerging research fields created by the current economic and environmental issues, such as solar cells, photovoltaics, photocatalysts, photothermal agents, and electrocatalysts for the HER and CO 2 reduction reactions 30‐38 . A few studies were performed to explore the applicability of Cu x S y for the HER and CO 2 reduction, which revealed that Cu‐based materials could be used in energy storage devices and major CO 2 converters 30,39‐41 …”
Section: Introductionmentioning
confidence: 99%